PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO ONLINE BUKALAPAK.COM - Sari, Novita; Saputra, Muhammad; Husein, Jamaluddin (Jurnal Manajemen Magister Darmajaya, 2017)
Bukalapak.com is one of the leading online companies in Indonesia owned by PT Bukalapak. to survive in a competitive business, the company must have an advantage so as to attract consumer purchasing decisions. This research will see the effect of Electronic Word Of Mouth on Purchasing Decision on Bukalapak.com. Sampling method used in this research is non probability sampling by using purposive sampling technique with number of sample 100 respoden. Data analysis in this study using Simple Linear Regression. The results of this study indicate the existence of word of mouth mouth to purchase decision.Keywords: Electronic Word of Mouth, Purchase Decision, OnlineÂ